Possibilities of Improving Salt-Related Water Quality on a Hungarian River - Hancz, Gabriella (International Journal of Engineering and Management Sciences, 2017)
The purpose of the study was the assessment of the salt related quality of river Kösely and its tributaries and to determine with calculations whether it is feasible to achieve improvement of the demonstrated water quality by the means of dilution in the frame of a PhD study. Besides data collection a series of twenty-eight Electrical Conductivity (EC) measurement was carried out at eleven sites along the river system. The resulting EC values all year long on every reach of the river exceeded even the tolerable values specified as irrigation water quality criteria and water quality standards in the Water Framework Directive. In the paper, we introduce the results of the survey along with authority surveillance data series from earlier years. Investigations in the water using anthropogenic activities causing this special water quality problem were also carried out and the results – quantitative and qualitative aspects as well – are introduced here. Since the pollutant is a conservative material, the calculations were performed using the simple dilution equation which is based on the law of conservation of mass. The findings of the calculations were the identification of those reaches of the river system where adequate water quality can be achieved by dilution considering the limiting factor of water delivery capacity. Our conclusion is that under current conditions of water management and water using activities there is no way to meet quality requirements with dilution. This can be achieved only by prevention or reduction of salt load.